The given expression is: 9 + (-7) + 8 + 2892 + 2929 + 373838 + (29082 * 2 * 8283828488383873)
To simplify it, we can start from the innermost parentheses:
= 9 + (-7) + 8 + 2892 + 2929 + 373838 + (29082 * 2 * 8283828488383873)
Next, we solve the multiplication inside the parentheses:
= 9 + (-7) + 8 + 2892 + 2929 + 373838 + (57764 * 8283828488383873)
Now, we calculate the value inside the remaining parentheses:
= 9 + (-7) + 8 + 2892 + 2929 + 373838 + (477723942509845572)
Finally, we add up all the numbers:
= 9 + (-7) + 8 + 2892 + 2929 + 373838 + 477723942509845572
= 477723942510210243
What's 9+-7+8+2892+2929+373838+(29082(2)(8283828488383873
1 answer